Musica enchiriadis and Scolica enchiriadis - Erickson, Raymond; Palisca, Claude V. 1921-2001 (New Haven & London Yale University Press, 1995)
This book provides the first complete English translation of two significant early music theory texts, the so-calledMusica enchiriadisand its longer companion, theScolica enchiriadis. Written in the late ninth century, both texts influenced many subsequent medieval authors.The two treatises are most famous for providing the earliest descriptions of organum, the oldest form of Western polyphony. They also include the oldest notated forms of many chant melodies, a more developed theory of the modes than found in Aurelian and other early theoretical writings, information about performance practice (including rhythm and the use of instruments), and numerous references to and quotations from a wide range of earlier authors, from Vergil through Augustine to Boethius. The treatises are introduced by an essay that places them in their historical context, showing their debt to earlier intellectual and musical traditions, their connection to then-current musical thought and practices, and their relationships to later writings on music.
Keywords: Music theory